PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, SET KESEMPATAN INVESTASI (IOS) DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA - Kurniawati Kurniawati (Universitas Bunda Mulia, 2017)
The quality of earnings reported in the financial statements is one of the key factors to make a decision. This study aims to examine the effect of the mechanism of Good Corporate Governance (GCG), which is proxied by board of commissioner and institutional ownership, the investment opportunity set and the size of the company to the quality of earnings.The sample used in this researchwere LQ45 companies listed at the Indonesia Stock Exchange during 2012-2015.Samples are collected by purposive sampling and resulted in 15 firms as the final sample. The statistic method used was multiplied analysis linear regression, with hypotheses testing of statistic t tests (α = 5%).The results of this research showed that the institutional ownership has a significant influence to the quality of earnings, while board of commissioner, investment opportunity set and the size of the company has no significant influence to the quality of earnings.Keywords : good corporate governance, board of commissioner, institutional ownership, investment opportunity set, size of the company, quality of earnings.